Aminoglycoside-based novel probes for bacterial diagnostic and therapeutic applications. Issue 8 (9th December 2016) - Zhang, Qingyang; Wang, Qinghua; Xu, Shengnan; Zuo, Limin; You, Xuefu; Hu, Hai-Yu
Abstract : A theranostic agent for broad spectrum pathogenic bacterial imaging and MRSA growth inhibition was developed. Abstract : Specific detection of pathogens has long been recognized as a vital strategy in the control of infectious diseases. Two novel theranostic neomycin analogs exhibit efficient targeting, labelling and killing of broad spectrum bacteria while not damaging macrophage-like cells. Furthermore, lipidated probe2 clearly showed antibacterial activity against methicillin-resistant S. aureus .